Unraveling DINCH – Induced hepatotoxicity mechanisms via network toxicology and molecular docking with experimental validation - Jingxin Xin; Changxu Zhou; Ying Wang; Huiqi Chen; Keling Yin; Ling Gao; Shanshan Shao (Ecotoxicology and Environmental Safety)
Phthalates, as a class of known endocrine disruptors, have been controversial because of their potential carcinogenicity and toxicity. Diisononyl cyclohexane-1,2-dicarboxylate (DINCH) is considered to be less toxic and more prone to environmental degradation, and is widely used as a substitute for phthalate. With the increasing use of DINCH in consumer products and industrial materials, the frequency of its detection in the air and human urine has also increased, which has aroused concern about its potential toxicity in food safety. Despite the increasing popularity of DINCH, toxicological studies on this topic are still limited. This study first predicted the hepatotoxicity and carcinogenicity of DINCH via the ADMETlab 3.0 platform. Next, the potential hepatotoxic genes associated with DINCH were collected through multiple databases, and a gene network was constructed. Through proteinprotein interaction, GO enrichment and KEGG pathway analyses, we elucidated the primary mechanism by which DINCH may induce hepatotoxicity. The expression of the selected key genes in related diseases was subsequently validated via the liver cancer database of TCGA and the NASH dataset of GEO. In addition, molecular docking technology and dynamics simulation were used to simulate the interaction and binding ability between DINCH and the core target. Cell experiments verified that DINCH increases hepatotoxicity primarily by upregulating TNF, TP53, and PPARG. In summary, this study elucidates the potential biological mechanisms of DINCH-induced hepatotoxicity, providing new scientific insights for the prevention and management of related toxicities.